Efficacy of Teachers Training Paraprofessionals to Implement Peer Support Arrangements. (April 2016) - Brock, Matthew E.; Carter, Erik W.
Although peer support arrangements are a promising strategy to promote inclusion in general education classrooms, previous studies have not addressed how paraprofessionals might implement this strategy under typical circumstances without extensive researcher involvement. In this single-case design study, four special education teachers trained and supported four paraprofessionals to implement peer support arrangements through delivery of a professional development package consisting of an initial orientation, video modeling, and brief coaching with performance feedback. Teachers implemented the professional development accurately, paraprofessionals implemented peer support arrangements with fidelity, and three of the four middle school students with severe disabilities increased their social interactions with peers while maintaining previous levels of academic engagement. These findings suggest a possible avenue for equipping paraprofessionals to implement peer support arrangements. Recommendations for preparing teachers to train and support paraprofessionals to implement intervention strategies are offered along with directions for future research.